Hubungan kausatif kualitas lingkungan dan kemiskinan di Jawa Timur - Fitriana Zahroh; Endan Suwandana (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Both poverty alleviation and environmental management cannot be separated from Sustainable Development Goals (SDGs). Development is carried out in an integrated manner in all dimensions: economy, environment, and social. The poor have a high dependence on the environment so that it is suspected to cause a decrease in environmental quality. On the other hand, the declining quality of the environment will further exacerbate the poverty condition of the community. This study aims to see the causal relationship between poverty and environmental quality, and vice versa, in East Java. Panel data analysis of 38 regencies in East Java during 2018-2021 shows that increasing poverty has a negative impact on environmental quality. On the other hand, a decrease in environmental quality also has an impact on an increase in the number of poor people. Thus, in East Java, due to that causal relationship, poverty alleviation policies can be carried out in line with the improvement of environmental quality.